Legal Position On Credit Financing For Creative Economy Actors With Guaranteed Trademark Rights Certificates - Hediati, Febri Noor; Kuspraningrum, Emilda; Utomo, Setiyo (Jurnal Independent, 2024)
Abstract Indonesia is one of the developing countries, one of which is in the field of trade or business. In the field of trade or business such as intellectual property rights. Many creative economy business actors in the UMKM industry in Indonesia, the UMKM industry is an economic sector that directly involves the creative economy community so that it is used as a support for the country's economy. For this reason, the government passed a regulation regarding the ease of obtaining financing in the development of an intellectual property-based creative economy for business actors in the world of trade. So that in this paper examines the legal position of credit financing for creative economic actors with trademark property rights as credit collateral. So that in the future the creative economy business actors can maximise the potential by producing quality products and have economic value. This writing uses a research method with a normative juridical approach conducted by examining library materials with a doctrinal approach. The results of this study are the first to formulate the legal position on the provision of credit financing for creative economic actors with trademark property rights as credit guarantees. This is because there is economic value in almost all intellectual property rights, especially in trademark rights, and as a legal subject, creative economy owners register with the Directorate General of IPR to obtain legal protection from the government with the issuance of IPR certificates. Later the intellectual property rights certificate can be used as a form of collateral from the credit financing process in banks or non-banks. The second effort made by the government to support the development of creative economy businesses by issuing PP no. 24 of 2022 which regulates credit financing based on intellectual property rights with the guarantee of IPR certificates.